1993
DOI: 10.1073/pnas.90.8.3202
|View full text |Cite
|
Sign up to set email alerts
|

Calcium influx mediated by the Escherichia coli heat-stable enterotoxin B (STB).

Abstract: The al. (13, 14) indicates that STB induces a rapid short-circuit current across porcine intestinal mucosa. Evidence for chloride transport was not observed, yet electrogenic anion secretion, possibly bicarbonate, was observed in the absence of elevated cyclic nucleotides (14,15). Beyond these few studies, nothing is known of the mechanism of STB action.Evidence that suggests a receptor-mediated mode of STB action includes short-circuit current responses when toxin is delivered to the mucosal, but not serosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 33 publications
0
62
0
1
Order By: Relevance
“…The activation of caspase-3 observed in our study could therefore be partially responsible for the influx of calcium observed during STb-mediated diarrhea [13] suggesting a link between the diarrheagenic and apoptotic pathways stimulated by STb. Indeed, studies conducted on Clostridium perfringens enterotoxin revealed that this toxin is capable of increasing intracellular calcium levels during both diarrhea [43] and apoptosis [44] and of inducing histological damages to the intestine [43] similar to the ones observed for STb [20].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The activation of caspase-3 observed in our study could therefore be partially responsible for the influx of calcium observed during STb-mediated diarrhea [13] suggesting a link between the diarrheagenic and apoptotic pathways stimulated by STb. Indeed, studies conducted on Clostridium perfringens enterotoxin revealed that this toxin is capable of increasing intracellular calcium levels during both diarrhea [43] and apoptosis [44] and of inducing histological damages to the intestine [43] similar to the ones observed for STb [20].…”
Section: Discussionmentioning
confidence: 83%
“…STb is then internalized by cells resulting in the stimulation of a pertussis toxin-sensitive GTP-binding regulatory protein [13]. This causes an influx of extracellular calcium ions [13] through a receptor-dependent ligand-gated calcium channel activating calmodulin-dependent kinase II [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le calcium intracellulaire active le métabolisme de l'acide arachidonique pour la synthèse de la prostaglandine E2 (PGE2) [46], mais la voie principale serait celle de la calmoduline [47]. Les différentes étapes seraient les suivantes : 1) la toxine STb se fixe à un récep-teur membranaire, le sulfatide [125,126] qui activerait une protéine G, stimulant l'ouverture d'un canal et l'entrée du Ca 2+ extracellulaire dans la cellule [31], 2) le Ca 2+ intracellulaire active la calmoduline, une protéine complexant le Ca 2+ , qui à son tour active la kinase II dépendante de la calmoduline [47], 3) la kinase II activée va probablement catalyser la phosphorylation de certaines protéines, telles que des protéines membranaires de transport des ions (pour illustration voir [33]). …”
Section: Voie Du Calciumunclassified
“…In vitro studies have shown that the intestinal secretion pathway involves the activation of a GTP-binding regulatory protein (G α i3 protein) sensitive to pertussis toxin. This action results in an intracellular calcium elevation through a receptor-dependent ligand-gated Ca 2+ channel [3]. The ensuing high level of intracellular Ca 2+ is presumably involved in activation of a calmodulin-dependent protein kinase II (CaMK II) which could open an undetermined ionic channel [8].…”
Section: Introductionmentioning
confidence: 99%